2012
DOI: 10.1007/s00381-012-1759-z
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric meningiomas in The Netherlands 1974–2010: a descriptive epidemiological case study

Abstract: ObjectiveThe purpose of this study was to review the epidemiology and the clinical, radiological, pathological, and follow-up data of all surgically treated pediatric meningiomas during the last 35 years in The Netherlands.MethodsPatients were identified in the Pathological and Anatomical Nationwide Computerized Archive database, the nationwide network and registry of histopathology and cytopathology in The Netherlands. Pediatric patients of 18 years or younger at first operation in 1974–2009 with the diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 27 publications
4
40
0
3
Order By: Relevance
“…There is also a higher frequency of WHO grade II and WHO grade III tumors in the <20 year age group than seen in older age groups and they are more frequently multiple. [5,6,23,26,30,31,33] Ionizing radiation is a risk factor for both pediatric and adult patients because of the long latency period involved in the development of post-radiation brain tumors; other possible etiological factors such as cranial trauma or viruses have not been conclusively shown to have a role in the pathogenesis of meningiomas [5,6,19,23,25,26,30,31,33]. Most of the studies in the literature focus on the clinical and histological characteristics of meningiomas in patients <20 years of age ( Table 6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also a higher frequency of WHO grade II and WHO grade III tumors in the <20 year age group than seen in older age groups and they are more frequently multiple. [5,6,23,26,30,31,33] Ionizing radiation is a risk factor for both pediatric and adult patients because of the long latency period involved in the development of post-radiation brain tumors; other possible etiological factors such as cranial trauma or viruses have not been conclusively shown to have a role in the pathogenesis of meningiomas [5,6,19,23,25,26,30,31,33]. Most of the studies in the literature focus on the clinical and histological characteristics of meningiomas in patients <20 years of age ( Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…The average age in those studies was between 10 and 15 years, [5,6,18,23,26,30,31,33] while the average age in our patient cohort was 25 years. It is possible that this is a reflection of the referral pattern to our practice and the representation of a more adult population accounted for this difference.…”
Section: Genetic Predisposition To Intracranial Meningiomamentioning
confidence: 99%
See 1 more Smart Citation
“…La présentation clinique de la NF2 chez l'enfant est particulière. L'âge médian de découverte de la maladie est de 13 ans, la majorité des patients étant âgée entre 12 et 18 ans [2,8,9]. Les premiers symptômes ne sont pas ceux liés à des schwannomes vestibulaires, mais plutôt à l'existence d'un méningiome, ou d'une tumeur spinale ou à la présence de schwannomes cutanés [3,8].…”
Section: Discussionunclassified
“…[5] An epidemiological study from the Netherlands showed that the overall meningioma incidence in children and adolescents is approximately 1: 1,700.000/year. [15] Due to the rarity of these lesions, large prospective studies are not available. By contrast, there are a relatively large number of single-center retrospective studies, compromising patients, within the literature.…”
Section: Introductionmentioning
confidence: 99%